171 Amphiphysin ii (bin1) driven transverse tubule formation in cardiac muscle. (5th June 2017) - Caldwell, Jessica; Taylor, Rebecca; Eisner, David; Dibb, Katharine; Trafford, Andrew
Abstract : Transverse (t)-tubules are vital for maintaining normal contractility of the heart through the tight regulation of excitation coupling. In cardiac disease, such as heart failure, t-tubule loss is closely associated with decreased synchrony of calcium release from the sarcoplasmic reticulum, resulting in impaired contractility. Thus, determining the mechanisms that control t-tubule formation is essential for understanding cardiac disease. Evidence suggests that the protein Amphiphysin II (AmpII) controls t-tubule formation in cardiac muscle and thus, may play a vital role in calcium regulation. Several studies, including our own, have shown that gene silencing of AmpII causes t-tubule loss in both skeletal and cardiac muscle. Furthermore, in non-muscle cells that usually lack t-tubules, expression of some variants of AmpII led to tubule formation. We therefore aimed to extend these observations and determine if AmpII is sufficient to drive t-tubule formation in the heart. Neonate rat ventricular myocytes (NRVMs) were isolated from 2 day old rats and maintained in culture. Vectors encoding isoforms 5, 8 and 9 of the AmpII gene (Bin1) with a C-terminal mKate2 fluorescent protein tag were transiently expressed in NRVMs using FuGENE 6 lipofection. A vector containing the mKate2 fluorescent tag only was used as negative control. After 48 hours, over-expression of Bin1 was confirmed at both the mRNA and protein level. Tubule formation was assessed using the membrane dye FM-464 and confocal microscopy. Of cells successfully transfected with Bin1, 95% had developed tubule structures. Conversely, tubules were absent in cells only expressing the fluorescent tag (p<0.001). Furthermore, Bin1 isoform 8 expression led to formation of more tubule structures when compared to isoform 5 and 9 (p<0.05). To determine if Bin1 driven tubules are functional, transfected cells were loaded with the Ca2+ indicator Fluo-8 AM and field stimulated. When compared with untransfected myocytes, expression of Bin1 isoforms 5, 8 and 9 increased the amplitude of the systolic calcium transient (p<0.05). Furthermore, transfection with Bin1 isoforms 5 and 9 led to faster rise and decay of the systolic calcium transient (p<0.05). Transfection with the control vector only had no effect on the calcium handling when compared with untransfected cells. Over-expression of Bin1 isoforms 5, 8 and 9 led to the formation of tubular structures in NRVMs. Whilst Bin1 isoforms 8 appears to play more of a role in tubule formation in NRVMs, these data suggest that other Bin1 isoforms (5 and 9) may enhance calcium kinetics. These data therefore suggest that Bin1 plays a vital role in tubule formation and development in cardiac myocytes. Given the importance of t-tubules to normal excitation contraction coupling and their perturbation in heart failure we therefore suggest that Bin1 might be a novel therapeutic target.